2021
DOI: 10.3389/fspas.2021.739046
|View full text |Cite
|
Sign up to set email alerts
|

Systems Astrochemistry: A New Doctrine for Experimental Studies

Abstract: Laboratory experiments play a key role in deciphering the chemistry of the interstellar medium (ISM) and the formation of complex organic molecules (COMs) relevant to life. To date, however, most studies in experimental astrochemistry have made use of a reductionist approach to experimental design in which chemical responses to variations in a single parameter are investigated while all other parameters are held constant. Although such work does afford insight into the chemistry of the ISM, it is likely that s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 72 publications
2
6
0
Order By: Relevance
“…Moreover, our primary aim in this present study was to determine whether any changes in the physico-chemical evolution of an astrophysical ice undergoing electron irradiation could be induced solely via a change in the phase of the ice, thus necessitating the adoption of an OFAT approach. The results of this study confirm the importance of considering the effect of ice phase in determining the outcome of a radiation astrochemistry experiment, and so highlight the need to build this parameter into more exhaustive systems astrochemistry experiments [82].…”
Section: Astrochemical Implicationssupporting
confidence: 68%
See 2 more Smart Citations
“…Moreover, our primary aim in this present study was to determine whether any changes in the physico-chemical evolution of an astrophysical ice undergoing electron irradiation could be induced solely via a change in the phase of the ice, thus necessitating the adoption of an OFAT approach. The results of this study confirm the importance of considering the effect of ice phase in determining the outcome of a radiation astrochemistry experiment, and so highlight the need to build this parameter into more exhaustive systems astrochemistry experiments [82].…”
Section: Astrochemical Implicationssupporting
confidence: 68%
“…This work is a typical example of a one-factor-at-a-time (OFAT) study, in which one experimental parameter (in this case, the phase of the ice under consideration) is varied and the results of such variation on the resultant physico-chemical evolution of the ice is analysed [81]. It has been suggested that such OFAT studies may not be ideal in revealing the true chemical complexity of an astrochemical reaction or process, and that statistically designed experiments and systems science approaches may be more appropriate [82].…”
Section: Astrochemical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, to the best of our knowledge, no previous study has included the RAI and Ih phases in such a comparative and systematic investigation. Our work therefore represents a progression in our understanding of the phase dependence of the radiation physics and chemistry of H 2 O astrophysical ices, thus allowing this parameter to be better incorporated into more exhaustive and relevant future experiments performed using a systems astrochemistry approach [47]. We have also interpreted our results in light of the new conclusions presented by Mifsud et al with regards to the role of hydrogen-bonds in impeding the radiolytic decay of crystalline ices [46].…”
Section: Introductionmentioning
confidence: 57%
“…However, fewer experiments have sought to investigate the effects of simultaneously changing multiple parameters on the resultant chemistry, despite this likely being more appropriate in terms of simulating astrophysical chemistry. Such an experimental approach is the basis of systems astrochemistry [47], and the data provided by this and similar studies will no doubt be useful in building up these more exhaustive and complete astrochemical experiments.…”
Section: Oh + Oh → H2o2mentioning
confidence: 94%